2018
DOI: 10.1159/000488033
|View full text |Cite
|
Sign up to set email alerts
|

Mortality and Stroke Recurrence in a Rehabilitation Cohort of Patients with Cerebral Infarcts and Chagas Disease

Abstract: Background: Chagas disease is related to ischemic stroke (IS), although few epidemiological studies have evaluated the associated mortality and recurrence. Our objective is to determine factors associated with mortality and recurrence of IS in patients with IS and Chagas disease. Methods: We retrospectively studied data obtained from electronic medical records of patients admitted at SARAH Hospitals across Brazil between 2009 and 2013. Using Cox regression analysis for mortality and logistic regression for rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 38 publications
(59 reference statements)
1
3
1
Order By: Relevance
“…Our multivariable analysis showed that neoplasms were associated with mortality in people with CD, while cardiopathy was not. These results are different from other series in endemic countries [ 32 , 33 , 34 , 35 ]. It can be a different treatment of cardiopathy available in our country as transplantation or use of Internal atrial defibrillation.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Our multivariable analysis showed that neoplasms were associated with mortality in people with CD, while cardiopathy was not. These results are different from other series in endemic countries [ 32 , 33 , 34 , 35 ]. It can be a different treatment of cardiopathy available in our country as transplantation or use of Internal atrial defibrillation.…”
Section: Discussioncontrasting
confidence: 99%
“…In contrast, just a third of the deaths in our study were considered to be directly related to CD. Of those associated with other diseases, the main cause of death was neoplasms (including lymphoma/leukemia), which is consistent with the main cause of non-CD death among people with CD in epidemiological studies in endemic countries [ 35 ]. Our multivariable analysis showed that neoplasms were associated with mortality in people with CD, while cardiopathy was not.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…e recovery period of CI, as a transitional stage from acute stage to sequela stage, is closely related to the recovery of neurological function and prognosis of patients. Some scholars have reported that active management after CI patients are stable can reduce the risk of recurrence of CI by 90% [4]. erefore, it is of great significance to give patients with CI scientific rehabilitation nursing during their recovery period.…”
Section: Introductionmentioning
confidence: 99%
“…14 Some additional challenges for secondary stroke prevention in Brazil are income inequality, aging of the population, higher rates of cardiovascular risk factors in the young and CD, known to be related to higher mortality and recurrence risks. [15][16][17][18] In efforts to improve this reality, the "Line of Care for People with Stroke" published in 2012 also included recommendations of implementation of evidence-based protocols, rehabilitation, outpatient care, and social reintegration. 19 An essential aspect of this regulation was the inclusion of key performance indicators for monitoring disease management in all stroke centers, including: (a) hospital discharge on antithrombotic therapy, (b) hospital discharge on anticoagulation therapy in patients with atrial fibrillation or flutter, (c) hospital discharge on statin therapy in patients with atherothrombotic mechanisms, (d) secondary prevention therapy, and (e) rehabilitation on hospital discharge.…”
Section: Secondary Preventionmentioning
confidence: 99%